2011
DOI: 10.1371/journal.pone.0015855
|View full text |Cite
|
Sign up to set email alerts
|

Social Requests and Social Affordances: How They Affect the Kinematics of Motor Sequences during Interactions between Conspecifics

Abstract: The present study aimed at determining whether and what factors affect the control of motor sequences related to interactions between conspecifics. Experiment 1 demonstrated that during interactions between conspecifics guided by the social intention of feeding, a social affordance was activated, which modified the kinematics of sequences constituted by reaching-grasping and placing. This was relative to the same sequence directed to an inanimate target. Experiments 2 and 4 suggested that the related-to-feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
65
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 24 publications
14
65
1
Order By: Relevance
“…Studies have reported differences in the reach-to-grasp phases of throwing and placing actions (Marteniuk, MacKenzie, Jeannerod, Athenes, & Dugas, 1987), lift and show actions (Ferri et al, 2011) and feed and place actions (Ferri et al, 2010;Flindall & Gonzalez, 2013). As has been previously demonstrated, participants in the current investigation produced smaller MGAs when the target object was to be placed in the mouth, rather than simply in a location near the mouth.…”
Section: Discussionsupporting
confidence: 70%
“…Studies have reported differences in the reach-to-grasp phases of throwing and placing actions (Marteniuk, MacKenzie, Jeannerod, Athenes, & Dugas, 1987), lift and show actions (Ferri et al, 2011) and feed and place actions (Ferri et al, 2010;Flindall & Gonzalez, 2013). As has been previously demonstrated, participants in the current investigation produced smaller MGAs when the target object was to be placed in the mouth, rather than simply in a location near the mouth.…”
Section: Discussionsupporting
confidence: 70%
“…This result is consistent with recent findings obtained during pick-and-place tasks, indicating that a social affordance was activated when they interact with a human being compared to a non-human agent (Becchio, Sartori, Bulgheroni, & Castiello, 2008;Ferri, Campione, Volta, Gianelli, & Gentilucci, 2011). Participants in Becchio et al's study computed a more appropriate kinematic approach when both picking and placing an object onto a human hand, inferring a more ''careful'' strategy when interacting with a human being.…”
Section: Human Vs Non-human Interaction: Activation Of Social Affordsupporting
confidence: 88%
“…Concerning request gestures, this was observed in previous studies where the authors found that the kinematics of reaching-grasping and placing and those of reaching-grasping and lifting were altered by the request gestures “give-me-in-the-hand” (Sartori et al, 2009), “feed-me” (Ferri et al, 2011) and “pour” (Innocenti et al, 2012). The fact that gestures understanding and responses preparing are interlaced processes also comes from a fMRI study (Newman-Norlund et al, 2007).…”
Section: Introductionmentioning
confidence: 60%